2016
DOI: 10.5935/1415-2762.20160004
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Nursing Discharge Plan for Pregnant and High-Risk Puerperal Women

Abstract: RESUMOEstudo descritivo de abordagem quantitativa com o objetivo de validar um plano de alta de enfermagem para gestantes e puérperas de alto risco, por meio da técnica de Delphi. Fez-se a coleta de dados no período de outubro de 2013 a outubro de 2014. Constituíram a amostra 17 avaliadores, sendo 11 enfermeiros e seis médicos especialistas em Obstetrícia. Os resultados revelaram os cuidados mais relevantes para cada um dos diagnósticos listados, sendo elaborados cinco cuidados para o trabalho de parto prematu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
(7 reference statements)
1
7
0
1
Order By: Relevance
“…Given this context, studies highlight the importance of reliability as to the uniformity of each item of a scale, measured by the consistency of the evaluators' responses. These findings corroborate the results of this research (17)(18)(19) . A study carried out to validate a surgical safety checklist emphasized the reliability of a validated instrument as something that contributes with the professional in all areas of knowledge, allowing the recognition of avoidable risk situations, educational actions, and valuing the management to whom it is intended.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Given this context, studies highlight the importance of reliability as to the uniformity of each item of a scale, measured by the consistency of the evaluators' responses. These findings corroborate the results of this research (17)(18)(19) . A study carried out to validate a surgical safety checklist emphasized the reliability of a validated instrument as something that contributes with the professional in all areas of knowledge, allowing the recognition of avoidable risk situations, educational actions, and valuing the management to whom it is intended.…”
Section: Resultssupporting
confidence: 83%
“…This aspect concerns the evaluation of those who shall use the instrument, the target audience. Although it is very relevant, this aspect should not be used in isolation for validation (17) . Considering, in the process of validation, the analysis through Cronbach's alpha test, for the expert judges and the target audience, the results of 0.974 and 0.694, respectively, were deemed reliable, due to their proximity to the value 1.…”
Section: Resultsmentioning
confidence: 99%
“…Discharge plans are instruments that allow organization of care, according to the needs of each patient, and begins at admission, with participation of an interdisciplinary team. 5 Planning hospital discharge makes it possible to reduce costs with hospitalizations, carry out continuity of care from hospital to home, reduce readmissions and minimize risks of hospital infection. Nurses are co-responsible for preparing patients and their families for hospital discharge; however, this practice has been little applied in hospital contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Nurses are co-responsible for preparing patients and their families for hospital discharge; however, this practice has been little applied in hospital contexts. 5 A study carried out in Sydney, Australia, showed that nurses who work in primary care with vulnerable children and families, elderly people with chronic conditions and mental health provide integrated care, including specialized care. Liaison nurses are encouraged to develop various domain areas such as coordinators, educators, communicators, advocates, change agents, managers, employees, negotiators, team leaders and clinicians.…”
Section: Introductionmentioning
confidence: 99%
“…Enferm. UFSM, Santa Maria, v10, p. 1-21, 2020 hemorragia, dificuldade em urinar ou respirar e nos casos em que o bebê apresente dificuldades de amamentação, esforço para respirar e não esteja reativo aos estímulos 23. Essa ação de orientação não foi adequada aos parâmetros da OMS, uma vez que as orientações elencadas pelos profissionais não contemplaram todos os sinais de perigo que merecem atenção nesse momento da LVPS.…”
unclassified